UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK SISWA KELAS IX DI MADRASAH TSNAWIYAH NEGERI 2 SAIPAR DOLOK HOLE KABUPATEN TAPANULI SELATAN - Siregar, Wiranto (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2023)
The background of this research is to look at the situation and condition of the students at MTsN 2 Saipar Dolok Hole, South Tapanuli Regency, which are far from the guidance of Islamic law inside and outside school. Therefore, as a researcher, I am very interested in raising this title with the aim of this research being to find out how the morals of students at MTsN 2 Saipar Dolok Hole are. Moral development is the first focus of attention in Islam. This can be seen from one of the apostolic missions of the Prophet Muhammad SAW. The main thing is perfecting noble character. The results of the study show that the moral condition of class IX MTsN students is good, but there are still some students who still need coaching. Based on the data that has been collected from the field, it can be known about how the morals of class IX students at Madrasah Sanawiyaah Negeri 2 Saipar Dolok Hole, South Tapanuli Regency, namely that student morals cannot be said to be good or striking are still in the unfavorable category because they have traits or habits that are still in the plebeian category, maybe because the location of the school is in the village, so the morals cannot be said to be good, even though their morals are not good, class IX students still have manners and courtesy towards teachers, both homeroom teachers in other fields of study and their friends who are at the school.